Information System of Land Use and Land Cover Change Based on Geospatial Data A Case Study in Batu Pahat, Johor - Sa'aidon, Amyraftri; Suhandri, Hendy Fitrian (Recent Trends in Civil Engineering and Built Environment, 2024)
Over the past few years, humans have always modified land to achieve the necessities for living, but the rate of exploitation was not as high as it is now. Land resources must be managed more efficiently in the future to assure that future generations can benefit from them. This study was conducted to identify land use changes in Batu Pahat area by integrating remote sensing and Geographical Information System (GIS) in developing land use and land cover map. Land use time series comparison between 2013 and 2020 was used in this study to discover changes in land use. In this research, data sets from Landsat 8 OLI satellite imagery used were obtained from United States Geological Survey (USGS). The satellite images were classified into several classes including water body, vegetation, built up area and barren land using the unsupervised classification technique. The use of ArcGIS software to analyze the data, revealed the changes in land usage in Batu Pahat area. The result indicates that there was an increase in area of built-up area and vegetation class by 11.01% and 2.02% respectively. Meanwhile, the area of water body reduced by 0.34% and barren land was reduced by 12.70%. The declination of barren land within seven years can be attributed to the increasing of built-up area due to urbanization and growth population in the study area.